2011
DOI: 10.5333/kgfs.2011.31.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Dry Matter Yield and Forage Quality at Mixture of Annual Legumes and Italian ryegrass on Paddy Field

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…Additionally, more excellent dry matter content, higher crude protein percent, and advanced water-soluble carbohydrates were obtained when wheat was intercropped with beans rather than sole wheat [3]. Furthermore, Italian Ryegrass and forage pea mixed cropping contributed to higher crude protein and dry matter content, and cultivation stability was improved [18]. Additionally, the most excellent mixed cropping system with alfalfa and ryegrass enhanced total seasonal DM production, reduced weeds, increased NDF concentration, improved digestibility, raised N concentration, and improved watersoluble carbohydrate (WSC) concentration [19].…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, more excellent dry matter content, higher crude protein percent, and advanced water-soluble carbohydrates were obtained when wheat was intercropped with beans rather than sole wheat [3]. Furthermore, Italian Ryegrass and forage pea mixed cropping contributed to higher crude protein and dry matter content, and cultivation stability was improved [18]. Additionally, the most excellent mixed cropping system with alfalfa and ryegrass enhanced total seasonal DM production, reduced weeds, increased NDF concentration, improved digestibility, raised N concentration, and improved watersoluble carbohydrate (WSC) concentration [19].…”
Section: Introductionmentioning
confidence: 97%
“…Many authors [Papoa et al 2012, Iqbal et al 2018, Manoj and Shekara 2020, Salama 2020] believe that fibre amount in the obtained feed is related to the cutting timing, plant development stage, plant morphological structure, share of individual components in the mixture as well as site and thermal conditions. According to Kim et al [2011], harvesting green forage at the right time is important for obtaining maximum nutritional value of forage. Forage plants when harvested at the vegetative stage have low yields and low fiber content.…”
Section: Introductionmentioning
confidence: 99%
“…When clover and wheat were intercropped, neutral detergent fiber (NDF) and acid detergent fiber (ADF) levels increased, according to the analysis by Contreras et al [ 16 ]. Additionally, Kim et al came to the conclusion that Italian ryegrass and fodder pea mixed cropping contributed to better crude protein and dry matter content, as well as improved cultivation stability [ 17 ]. Furthermore, some studies revealed that cereal–legume mixed cropping has an impact on the forage quality parameters such as relative feed value (RFV), relative forage quality (RFQ), total digestible nutrient (TDN), dry matter intake (DMI), digestible dry matter (DDM), and quality index (QI).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, one of the other most important factors that affect the quality of forage feed is the time of harvest. According to Kim [ 17 ], harvesting at the right time is crucial for obtaining the maximum nutritional value as well as lowering the danger of mold infection on the farm. Different harvesting times may compromise the quality of fodder, notably the forage nutritional value [ 11 ].…”
Section: Introductionmentioning
confidence: 99%